Evidence regarding the ecological benefits of payment for ecological services programs from China’s grassland ecological compensation policy - Wei, Cong; Zhou, Yingfeng; Kong, Jiayang (Frontiers in Environmental Science, 2022)
We provide evidence that payment for ecological services programs have had a significant and robust positive impact on grassland quality by focusing on China’s grassland ecological compensation policy (GECP)—the planet’s largest. Our baseline results are obtained from a difference-in-differences estimator, comparing counties which have and have not introduced a GECP. It shows that such a policy increases grassland quality by about four percentage points on average. We found a similar impact of the GECP on grassland quality when we controlled for the estimated propensity of a county to launch this policy based on a series of county characteristics, such as weather and economic conditions. We obtained comparable estimates when we used the propensity score to balance county characteristics between counties which have and have not launched the GECP. Our results also show that the policy has a larger impact on grassland quality in warmer, richer, and in less populated counties than those with the opposite characteristics. We found strong suggestions for the persistent impact of the GECP on grassland quality, implying that Chinese officials should persist with the policy and expand the range of the pilot policy. In addition, we carried out a series of robustness tests, including the leave-one-county-out test, bootstrapping test, and the permutation test, to illustrate the robustness of our results.